2006
DOI: 10.1369/jhc.5a6792.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Secretory Granule Protein Syncollin Localizes to HL-60 Cells and Neutrophils

Abstract: The secretory granule protein syncollin was first identified in the exocrine pancreas where a population of the protein is associated with the luminal surface of the zymogen granule membrane. In this study we provide first morphological and biochemical evidence that, in addition to its pancreatic localization, syncollin is also present in neutrophilic granulocytes of rat and human origin. By immunohistological studies, syncollin was detected in neutrophilic granulocytes of the spleen. Furthermore, syncollin is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…2). Role of these correlated proteins in the immune system has already been characterized in different species35363738394041. Several studies have also reported correlated expression of several immune related protein-coding genes with a single lncRNA13.…”
Section: Resultsmentioning
confidence: 96%
“…2). Role of these correlated proteins in the immune system has already been characterized in different species35363738394041. Several studies have also reported correlated expression of several immune related protein-coding genes with a single lncRNA13.…”
Section: Resultsmentioning
confidence: 96%
“…Specifically, it is a zymogen granule protein found on the inner surface of the granule membrane with a role in the concentration and maturation of zymogens, as well as in the regulation of exocytosis [17,18]. A few recent studies have described its presence and function in granules in other tissue types [19]. Syncollin has been identified in a qualitative proteomic analysis of pancreatic juice from patients with pancreatic cancer, and was elevated in serum from a murine model of pancreatic cancer [20,21]; however to our knowledge, this is the first report of its study and extended validation through ELISAs in human serum.…”
Section: Discussionmentioning
confidence: 99%
“…Several genes known to play a role in various inflammatory conditions were differentially modulated in our data set (Table 3 ). Such molecules include two elastase genes, Ela1 [ 67 ] and the neutrophil elastase Ela2 [ 68 ], known to play a role in peripheral tissues invaded by microbes [ 69 ], the Spp1 gene [ 70 ], and the secretory granule protein syncollin ( Sync ), expressed by neutrophils with a role in host defence to infections by invading bacteria, fungi, and protozoa [ 71 ]. Sync is also expressed in the exocrine pancreas and in the duodenum and colon [ 72 ].…”
Section: Discussionmentioning
confidence: 99%